2021
DOI: 10.3389/fphys.2021.782677
|View full text |Cite
|
Sign up to set email alerts
|

The CXCL1-CXCR2 Axis Mediates Tubular Injury in Diabetic Nephropathy Through the Regulation of the Inflammatory Response

Abstract: Diabetic nephropathy (DN) is one of the most severe complications of diabetes. Inflammation mediated by inflammatory factors is thought to accelerate the progression of renal damage in DN. However, which inflammatory factors mediate the inflammatory response in DN remains unclear. In this study, we determined that the CXCL1-mediated inflammatory response may play an essential role in DN progression through bioassays. Subsequently, we observed that the expression of CXCL1 and its receptor (CXCR2) was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Analysis of marker genes associated with the hypoxic response and kidney injury affirmed and extended our initial findings (Figure 2C). For example, injury and repair associated genes like GDF15 ( 50 ), TGFB1 ( 51 ), JUN ( 52 ), C-X-C motif chemokine ligand 1 ( CXCL1 ) ( 53 ), snail family transcriptional repressor 1 ( SNAI1 ) ( 54 ) and SOX9 ( 13, 55 ) were higher in the d20h group compared to control (Figure 2C). Hypoxia can cause cell cycle arrest through the induction of cell cycle inhibitors like CDKN1A ( 40, 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of marker genes associated with the hypoxic response and kidney injury affirmed and extended our initial findings (Figure 2C). For example, injury and repair associated genes like GDF15 ( 50 ), TGFB1 ( 51 ), JUN ( 52 ), C-X-C motif chemokine ligand 1 ( CXCL1 ) ( 53 ), snail family transcriptional repressor 1 ( SNAI1 ) ( 54 ) and SOX9 ( 13, 55 ) were higher in the d20h group compared to control (Figure 2C). Hypoxia can cause cell cycle arrest through the induction of cell cycle inhibitors like CDKN1A ( 40, 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…[697], IL18 [698], CYGB (cytoglobin) [636], EGF (epidermal growth factor) [699], TRPM2 [700], BANK1 [701], SORT1 [643], HSPG2 [645], NOX4 [702], MYH9 [703], TRPV4 [704], B4GALNT1 [705], LAG3 [706], CACNA1C [654], LRP5 [707], PIM1 [658], MDK (midkine) [708], CA2 [709], TRPC6 [710], CYP2D6 [711] and STAT4 [712] might be a biological target of type 1 diabetes mellitus. CCK (cholecystokinin) [713], IL33 [714], IRF4 [715], CXCL8 [716], MMP3 [717], DDIT4L [718], KL (klotho) [719], CXCL6 [87], CXCL1 [720], STC1 [721], PDK4 [722], RAB27B [723], CXCL5 [724], GPRC5A [725], TXNIP (thioredoxin interacting protein) [726], RAB3B [727], HSPA5 [728], DKK1 [93], NAMPT (nicotinamidephosphoribosyltransferase) [729], TNFAIP3 [730], GHR (growth hormone receptor) [731], ANXA1 [732], CD40 [733], KITLG (KIT ligand) [734], SMURF2 [735], NRG1 [684], GCLC (glutamate-cysteine ligase catalytic subunit) [685], NPHP1 [736], EPOR (erythropoietin receptor) [737], ADK (adenosine kinase) [738], SAA1…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tang et al. showed that in diabetic mice and DN patients, the expression level of CXCR2 was increased; when the CXCR1/CXCR2 axis was blocked, the renal inflammation and pathological damage in the kidneys of db/db mice could be relieved [ 35 ]. Dual specificity phosphatase 1 (DUSP1) is also known as mitogen‐activated protein kinase phosphatase 1 (MKP1).…”
Section: Discussionmentioning
confidence: 99%